Rethinking the Indonesian Muslim Identity Endorsed by Hanan Attaki's Popular Preaching on Social Media - hannan, abd (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2024)
Popular Islam constructed a new religious trend for millennial Muslim practice and identity on social media. This study discusses the Muslim religious identity circulated by Hanan Attaki as a millennial preacher in contemporary Islamic discourse in Indonesia. This article examines Attaki's preaching on his social media accounts using a digital ethnography study that focuses on Islamic populism toward the trend of new religious identity among millennial Muslims. The study shows that pop Islam in Attaki's preaching activities highlights contemporary elements regarding appearance, communication techniques, and religious topics of young millennial Muslims. These elements include visualization and self-image, as shown through his social media accounts such as Facebook, Instagram, and YouTube. However, the success of this preaching involves a disruption of religious identity for his followers. In addition to the superficial and passing religious knowledge that they absorb at a glance, those who are accustomed to studying religion only through social media will have great potential to trap millennial Muslims in extreme, excessive, and fanatic religious sentiments in views, attitudes, and behaviors instead of a predetermined and prescribed religious identity.